Nariva Ferry - (:unkn) unknown (Unknown, 2011)
The postcard shows a wooden punt which served as a ferry bridge over the Nariva and Ortoire rivers (1870s - 1950s) as there was no road to the district of Mayaro. The trip across the river used to cost a penny. People, horses, buggies and later automobiles were ferried across the rivers.
Colour: Sepia; Style: Landscape; Other: Bordered, Undivided
Keywords: Trinidad and Tobago; Postcards; Ferries--Trinidad and Tobago; Water taxis--Trinidad and Tobago; Inland water transportation--Trinidad and Tobago; Shipping--Trinidad and Tobago; Rivers--Trinidad and Tobago; Cities and towns--Trinidad and Tobago--Mayaro